Search for Higgs and Z Boson Decays to φγ with the ATLAS Detector - Onofre, A. (2016)
A search for the decays of the Higgs and Z bosons to a ϕ meson and a photon is performed with a pp collision data sample corresponding to an integrated luminosity of 2.7  fb−1 collected at s√=13  TeV with the ATLAS detector at the LHC. No significant excess of events is observed above the background, and 95% confidence level upper limits on the branching fractions of the Higgs and Z boson decays to ϕγ of 1.4×10−3 and 8.3×10−6, respectively, are obtained.